A profile of the Ethopian economy - Bequele, Assefa (Addis Ababa : Oxford University Press, 1969)
This work is addressed primarily to students of economics in the hope that it will provide them with supplementary reading material on their country's economy.
osc 28/01/2019
Loans
Keywords: Economic history; Ethiopia